About Some Issues of Teaching Foreign Languages Using Modern Educational Technologies - Jalolovna, Mirzaeva Mukhabat (Miasto Przyszłości, 2023)
The "Law on Education" is the driving force of the main directions of fundamental reforms carried out on the basis of the "National Curriculum for Personnel Training" and the document on Common European Language Competences. Advanced pedagogical technology is a field of knowledge that systematically forms 3,000-year-old revolutions, thirst for knowledge, love for the country, humanitarianism, spiritual and spiritual perfection. [1, 3-5p.].